Systems Pharmacology-Based Method to Assess the Mechanism of Action of Weight-Loss Herbal Intervention Therapy for Obesity - Zhou, Wei; Chen, Ziyi; Wang, Yonghua; Li, Xiumin; Lu, Aiping; Sun, Xizhuo; Liu, Zhigang (Frontiers in Pharmacology, 2019)
Obesity is a multi-factorial chronic disease that has become a serious, prevalent and refractory public health challenge globally due to the high rates of various complications. Traditional Chinese Medicines (TCM) as a functional food is considered to be a valuable and readily available resource for treating obesity owing to their better therapeutic effects and lower side effects. However, its “multi- compounds” and “multi-targets” features make it extremely difficult to interpret the potential mechanism underlying the anti-obesity effects of TCM from a holistic point of view. An innovative systems-pharmacology approach was introduced, which combined the ADME screening, multiple target fishing, GO enrichment analysis, network pharmacology, as well as pathway analysis to explore the potential therapeutic mechanism of obesity and related diseases, exemplified by the weight loss herbal intervention therapy (W-LHIT). Our study will provide a promising approach to facilitate the development and discovery of new botanical drugs.